Music from the true vine : Mike Seeger's life & musical journey - Malone, Bill C. (Book collections on Project MUSE., 2011)
Malone's biographical work covers the life and musical contributions of folk artist Mike Seeger, the brother of folk singer Pete Seeger. One of the founding members of influential folk group the New Lost City Ramblers, Mike Seeger spent more than fifty years preserving, performing, and commemorating the culture and folk music of white and black Southerners, which he called "music from the true vine." Malone argues that Seeger, while not as well known as his brother, may be more important in his work to identify and give a voice to the people from whom the Folk Revival borrowed its songs. Malon.